2007
DOI: 10.1530/rep-07-0061
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism by murine ovarian follicles and oocytes grown in vitro

Abstract: Metabolic markers are potentially valuable for assessment of follicle development in vitro. Carbohydrate metabolism of murine preantral follicles grown to maturity over 13 days in vitro has been measured, and metabolism of resulting oocyte-cumulus complexes (OCCs) and denuded oocytes has been compared with in vivo ovulated control counterparts. Spent follicle culture media were analysed for glucose, lactate and pyruvate concentrations. During follicle in vitro growth, glycolysis accounted for a rise from w24 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 50 publications
4
53
0
3
Order By: Relevance
“…Previous work has shown that oocytes have low glycolytic activity [74] as well as low phosphofructokinase (PFK) activity [75]. As described above, the oocyte and cumulus cells exist together until after fertilization as the cumulus-oocyte-complex (COC).…”
Section: Glucosementioning
confidence: 99%
“…Previous work has shown that oocytes have low glycolytic activity [74] as well as low phosphofructokinase (PFK) activity [75]. As described above, the oocyte and cumulus cells exist together until after fertilization as the cumulus-oocyte-complex (COC).…”
Section: Glucosementioning
confidence: 99%
“…Therefore, we suggest that endogenous gonadotropins, LH, FSH and CG, up-regulate expression of ENO2 in oocytes and theca cells of preantral and antral follicles, which would activate glycolysis in these cells. Glycolysis is a major contributor to energy production in ovarian follicles [6][7][8]. Thus, gonadotropin-stimulation of the glycolysis in oocytes and theca cells would activate ovarian functions such as follicle growth and maturation, and hormone production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, serum gonadotropin levels are low at metestrus [15, sure to hCG stimulates glycolytic activity in ovarian follicles [8,9] and that glycolysis in ovarian follicles is required for follicle growth and estradiol secretion [9]. In addition, the expression of ENOs varies according to the pathophysiological, metabolic or developmental conditions of cells [1,12], e.g., the levels of ovarian ral and antral follicles [12,[23][24][25], demonstrating that oocytes metabolize glucose via glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations